Bullying Experience Among Trainees of Moral Rehabilitation School - Wazir, Mohd Nor Hafiz Bin Mohd; Chethiyar , Saralah Devi Mariamdaran (International Journal of Rehabilitation and Special Education (IJRSE), 2024)
Bullying is one of the criminal misconduct or deviant behaviour that occurs in society today. This bullying activity is also common among teenagers either at the school or tertiary level. This problem also occurs among juvenile trainees who are undergoing rehabilitation in correctional institutions. This quantitative study was conducted to explore the issues and problems of bullying based on the actual experience of the respondents. A total of 109 trainees of the Moral Rehabilitation School were selected using purposive sampling. The research data were collected by employing the questionnaires with a structured self-completed instrument known as the Revised Malaysian Bullying Questionnaire (RMBQ). The findings of this study indicate that the participants in this study report receiving and perpetrating relatively low amounts of bullying. Further, the findings of the study revealed that the level of bullying among the trainees of Moral Rehabilitation School differ in terms of gender. The suggestion from the findings of this study is that the Moral Rehabilitation School should raise awareness among trainees by conducting bullying awareness programs and awareness campaigns.